Architecture and the Novel under the Italian Fascist Regime - Billiani, Francesca; Pennacchietti, Laura; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Palgrave Macmillan, 2019)
This book is open access under a CC BY 4.0 license (3z(BFrancesca Billiani and Laura Pennacchietti draw brilliantly and with precision the evolution of the new architecture and of the national novel (with insights on translations of international novels), whose profiles had been shaped from different angles, especially in the 1930s. These two fields, apparently so distant one from the other, had never been analysed in parallel. This book does this and uncovers several points of contact between the two, spanning propaganda and theoretical turning points.(3y $1 (BChiara Costa and Cornelia Mattiacci, Fondazione Prada, Italy (3z(BThis book shows convincingly how the arte di Stato during Fascism was created with the morality of a new novel as well as architecture. It is surprising to read how one of the representatives of State art, Giuseppe Bottai, is also one of the finest critics of realist novels and rationalist architecture. More than parallel endeavours, the system of the arts during the Fascist regime should be viewed as a series of intersections of cultural, political and aesthetic discourses.(3y $1 (BMonica Jansen, Utrecht University, The Netherlands Architecture and the Novel under the Italian Fascist Regime discusses the relationship between the novel and architecture during the Fascist period in Italy (1922-1943). By looking at two profoundly diverse aesthetic phenomena within the context of the creation of a Fascist State art, Billiani and Pennacchietti argue that an effort of construction, or reconstruction, was the main driving force behind both projects: the advocated (3z(Brevolution(3y (Bof the novel form (realism) and that of architecture (rationalism). The book is divided into seven chapters, which in turn analyze the interconnections between the novel and architecture in theory and in practice. The first six chapters cover debates on State art, on the novel and on architecture, as well as their historical development and their unfolding in key journals of the period. The last chapter offers a detailed analysis of some important novels and buildings, which have in practice realized some of the key principles articulated in the theoretical disputes. Francesca Billiani is Senior Lecturer in Italian Studies and Director of the Centre for Interdisciplinary Research in the Arts and Languages at the University of Manchester, UK. Laura Pennacchietti is Research Associate in Italian Studies at the University of Manchester, UK.s
1. National Novel and New Architecture -- 2. The Regime and the Creation of an 'Arte di Stato' -- 3. Constructing the Novel -- 4. Fascism and Architecture -- 5. 900 and Quadrante: Theorizing an Interdisciplinary Aesthetic Model -- 6. State Art, the Novel, and Architecture: Intersections -- 7. Novels and Buildings -- 8. Conclusion.
Keywords: Ethnology -- Europe; Culture; Cultural property; Arts; European literature; Architecture -- History; European Culture; Cultural Heritage; Fine Art; European Literature; Architectural History and Theory